Therapeutic effects of resveratrol and β-carotene on L-arginine-induced acute pancreatitis through oxidative stress and inflammatory pathways in rats - Arzu Gezer; Hilal Üstündağ; Mustafa Özkaraca; Ebru Karadağ Sari; Cihan Gür (Scientific Reports)
Abstract Acute pancreatitis (AP) is a severe inflammatory condition affecting the pancreas, often leading to systemic inflammation and organ dysfunction. This study evaluated the effects of resveratrol (RES) and β‐carotene (βC) on L-arginine-induced AP in rats. Forty-eight male Sprague Dawley rats were divided into six groups: Control (C), RES (20 mg/kg), βC (50 mg/kg), AP, AP + RES, and AP + βC. The AP model was induced with 250 mg/100 g L-arginine intraperitoneally twice daily with a 1-h interval. The AP group showed significantly elevated oxidative stress (MDA) and reduced GSH levels (p < 0.001). Immunohistochemical (IHC) staining with anti-insulin antibody revealed reduced β + langerhans islet size in the AP group. qPCR analysis indicated significant upregulation of inflammatory genes NF-κB, TNF-α, and IL-1β (p < 0.001), and apoptotic genes Bax and Caspase-3, with downregulation of Bcl-2 (p < 0.001). RES and βC treatments significantly reduced MDA levels and increased GSH levels (p < 0.01 for both) compared to the AP group. The AP + RES and AP + βC groups exhibited preserved β + Langerhans islet size (p < 0.01), suppressed NF-κB, TNF-α, and IL-1β expression, reduced Bax and Caspase-3 levels, and increased Bcl-2 levels (p < 0.01). Histopathological findings supported these results. RES and βC confer significant effects against L-arginine-induced acute pancreatitis by reducing oxidative stress, preserving pancreatic islet integrity, suppressing inflammatory responses, and modulating apoptotic pathways. RES demonstrated a slightly superior efficacy in reducing inflammation and oxidative stress markers, suggesting it may be more effective in treating acute pancreatitis.